Da diferenciação do sexo à diferença sexual: um estudo psicanalítico - Nunes, Viviane Soares (2016)
The interest for the theme of this dissertation came out from questions about the effects of the birth of children with Disorder of Sex Differentiation (DSD), genetic condition that often makes harder to identify the first definition of the sex: whether the baby is a boy or a girl. The sex differentiation, from the anatomic point of view, is settled since the distinction of the genitals and, from the genetic point of view, based on a karyotype exam. And from the psychic point of view, how does the sexual difference institute itself? This very research investigates the statute of the sexual difference into Freud‘s theory. The sexuality conception is discussed according to the drive notions, erogenous zone, sexual aberrations, bisexuality and Oedipus complex. Since the analysis of the ―Little Hans‖ case, stands out the importance of the infantile sexuality, the Oedipus complex and the castration complex into sexual difference, to the detriment of the anatomic and genetic aspects. It is concluded that the sex is a puzzle for any child and that the sexual differentiation institute itself around the phallus as a psychic representation.